Sintesis Komposit Magnetit/Hidroksiapatit Menggunakan Metode Hidrotermal Dengan Variasi Waktu Dan Konsentrasi FeCl3 - Bima Wandika Putra; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Magnetite / hydroxyapatite composite is a material that can be used as a drug carrier. The purpose of this study was analyzing variations in time and FeCl3 concentration on the characteristics of composites produced using the hydrothermal method. A total of 0.3248 gr FeCl3.6H2O (2 mmol or 0.05 M), sodium citrate 1.1764 gr (4 mmol or 0.10 M), and 0.3604 gr urea (6 mmol or 0.15 M) dissolved in 40 ml of distilled water, then 0.1 g of PEG (7.5 g/L) is added while stirring until it runs out, then added Hydroxyapatite powder as much as 30% by weight, stirring until it dissolves. After being put in a Teflon container. The container was put into an oven and set at 210 ° C. The reaction times used in this study were 5, 7, 9, 12 and 15 hours. Furthermore, it was carried out with the help of an external magnetic field (permanent magnet) so that the process can be carried out quickly and more effectively. Furthermore, it was settled by completion. The sample is then dried at oven temperature 120°C for 12 hours. The resulting composite powder was characterized by XRD, BET, TEM, and VSM. Increasing hydrothermal time to 15 hours at a concentration of 0.15 M, increasing the surface area of particles from 64.48 m2/gr to 67.41 m2 /gr. Where as the variation of higher FeCl3 concentration from 0.05 M to 0.15 M is the large size of magnetite crystals 18.41 nm to 22.77 nm. Variation of higher FeCl3 concentration enlarged the surface area of particles from 48.21 m2/gr to 67.41 m2/gr, increased magnetic saturation value from 13.24 emu / gr to 17.27 emu/gr, with the shape of the particles produced round shape measuring 15 nm.Keywords: composite, drug delivery, hydrothermal, hydroxyapatite, magnetite